Doxorubicin caused severe hyperglycaemia and insulin resistance, mediated by inhibition in AMPk signalling in skeletal muscle. Issue 5 (15th February 2016) - de Lima Junior, Edson Alves; Yamashita, Alex Shimura; Pimentel, Gustavo Duarte; De Sousa, Luís G. O.; Santos, Ronaldo Vagner T; Gonçalves, Cinara Ludvig; Streck, Emilio Luiz; de Lira, Fábio Santos; Rosa Neto, Jose Cesar
Abstract: Background: Cancer is considered the second leading cause of death in the world, and for the treatment of this disease, pharmacological intervention strategies are frequently based on chemotherapy. Doxorubicin (DOX) is one of the most widely used chemotherapeutic agents in clinical practice for treating a number of solid tumours. The treatment with DOX mimics some effects of cancer cachexia, such as anorexia, asthenia, decreases in fat and skeletal muscle mass and fatigue. We observed that treatment with DOX increased the systemic insulin resistance and caused a massive increase in glucose levels in serum. Skeletal muscle is a major tissue responsible for glucose uptake, and the positive role of AMPk protein (AMP‐activated protein kinase) in GLUT‐4 (Glucose Transporter type 4) translocation, is well established. With this, our aim was to assess the insulin sensitivity after treatment with DOX and involvement of AMPk signalling in skeletal muscle in this process. Methods: We used Wistar rats which received a single dose of doxorubicin (DOX group) or saline (CT group) intraperitoneally at a dose of 15 mg/kg b.w. The expression of proteins involved in insulin sensitivity, glucose uptake, inflammation, and activity of electron transport chain was assessed in extensor digitorum longus muscle, as well as the histological evaluation. In vitro assays were performed in L6 myocytes to assess glucose uptake after treatment with DOX. Agonist of AMPk [5‐aminoimidazole‐4‐carboxamide (AICAR)] and the antioxidant n‐acetyl cysteine were used in L6 cells to evaluate its effect on glucose uptake and cell viability. Results: The animals showed a significant insulin resistance, hyperglycaemia, and hyperinsulinemia. A decrease in the expression of AMKP and GLUT‐4 was observed in the extensor digitorum longus muscle. Also in L6 cells, DOX leads to a decrease in glucose uptake, which is reversed with AICAR. Conclusions: DOX leads to conditions similar to cachexia, with severe glucose intolerance both in vivo and in vitro . The decrease of AMPk activity of the protein is modulated negatively with DOX, and treatment with agonist of AMPk (AICAR) has proved to be a possible therapeutic target, which is able to recover glucose sensitivity in skeletal muscle.